(untitled) (OverHolland, 2013)
Jaap Evert Abrahamse en Jan van Doesburg Jerzy Gawronski (red.) Amsterdam Ceramics. A city’s history and an archaeological ceramics catalogue 1175-2011 Amsterdam (Bas Lubberhuizen) 2012, 336 pp. P.J. Knegtmans Amsterdam. Een geschiedenis Amsterdam (SUN) 2011, 440 pp. Peter Jan Knegtmans Amsterdam: een geschiedenis (‘Amsterdam: a history’) Amsterdam, SUN, 2011, 44